Deep insight into interaction mechanisms between ESBR and silica modified by different silane coupling agents. Issue 37 (17th February 2020) - Wang, Chen; Li, Ai; Kong, Miqiu; Yang, Qi; Lv, Yadong; Huang, Yajiang; Li, Guangxian
Abstract: In this study, the interaction mechanisms of different silane coupling agents on the mechanical properties, dynamic viscoelastic properties, and rheological properties of emulsion styrene‐butadiene rubber (ESBR)/silica composites were investigated. It is found that the comprehensive performances are improved by the addition of silane coupling agents and the optimal performance is exhibited in ESBR filled with 50 phr modified silica. Moreover, with the addition of the bis‐(3‐triethoxysilylpropyl)‐tetrasulfide modified silica, the wet skid resistance of composites is significantly enhanced by 14.0%, whereas by the addition of 3‐octanoylthio‐1‐propyltriethoxysilane modified silica, the rolling resistance is remarkably reduced by 19.6% and the processing safety is improved. It can be attributed to the increased bound rubber contents induced by the enhanced interactions between the modified silica and rubber matrix characterized by rheological properties. Furthermore, it is pointed out that the second layer bound rubber plays a dominant role in the improved properties of the composites. Abstract :